PENGARUH KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN LEMBAGA PENYIARAN PUBLIK RRI SURAKARTA - Sri Hartono, Novi Kusuma Pangestika, Djumali & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
The purpose of this study is To determine the influence of leadership, motivation and discipline on employee performance in Public Broadcasting RRI Surakarta. This study uses the population is all employees of the Public Broadcasting Institute RRI with the number of 207 employees. The research sample will be taken 30% from the total population (30% x 207) so that the sample of researchers as many as 66 people. This study uses multiple linear regression data analysis tools. The result of research proves the result of F test analysis known that the variable of leadership, motivation and discipline have influence together and significant to performance. The result of t test analysis is known that leadership variable has significant influence to performance. Motivation variable has a significant influence on performance. The discipline variable has a significant influence on performance.Keywords: Leadership, Motivation, Discipline, Performance